Simultaneous reduction and covalent grafting of polythiophene on graphene oxide sheets for excellent capacitance retention - Yadav S.K.; Kumar R.; Sundramoorthy A.K.; Singh R.K.; Koo C.M. (My University, 2025)
Herein, we report room temperature reduction and covalent grafting of graphene oxide sheets by thiophene derivatives to produce pseudocapacitive electrodes, which are capable of delivering high capacitance (230 F g-1 at 1 mV s-1) and, most important, 100% cycling retention after 5000 cycles. Raman and FTIR spectroscopies confirmed the strong interaction of PTh with rGO in the PTh-g-rGO hybrids. © 2016 The Royal Society of Chemistry.